An Adsorption Method for Characterization of Surface Area and Pore Size of Solid Surfaces - Andoni*, Adelaida; Xhaxhiu, Kledi; Taraj, Krenaida (Asian Journal of Chemistry, 2014)
This study focuses on an adsorption method aiming surface characterization of porous solids. Natural Albanian clay, activated carbon and a medicinal Albanian plant are considered for the current characterization. These materials are widely used in chemical industry. The surface characterizations of these porous materials intend the determination of specific surface area, total volume of pores and the distribution of pores by size. The above-mentioned determinations make possible the prediction of these porous materials behavior during physico-chemical processes carried out on their surfaces. Their characterization is carried out using the method of gases adsorption. In this context nitrogen is used as adsorption gas at 77 K. We found size of pores in the order of nanometer scale.